THE KINGDOM OF LEARNERS – WHAT THE LEARNING AND TEACHING LOOK LIKE - Barno, Abdullaeva; Abdusalomovich, Khalikov Azam; Shin (International Journal of Psychosocial Rehabilitation, 2020)
What the learning and teaching look like? This paper provides several thoughts at the conceptualization level that teacher as a re-creator who keeps improving her professions, understand the learners properly in any situation, restores the learner’s natural spontaneous learning and finally invites the learner for joyful parties in the kingdom of learners. For this process, friendly relationship between the teacher and the learner is essential. Since a child is born, she learns, practices, speaks, stands up and walks with both feet with curiosity and passion. At this time, if there is no one to care her around, she can’t talk or walk. There should be friendly and reciprocal relationship with the parents and learner with love. However, as a child grows, parents, school teachers and society deprive a child from curiosity and enthusiasm, therefore, spontaneous learning disappears and she lives with false life. After entering the university, she is free from influences of others to live up to her life. It is necessary to enjoy learning voluntarily in this environment and to live with endless improving and sharing what is learned. However, it is difficult for students to live with self-motivated and enjoyable learning by corporate demands to find a decent job in general. To understand what the learning and teaching look like in higher education, Several suggestions regarding learning and teaching based on two cases were provided. Didactic triangle and learning theories including connectivism were summarized. Transformative change in learning and teaching with limitation were discussed. Conclude what we have to do with the learners emphasizing that the learners should be properly understood.